Implementasi Kebijakan Gerakan Stop Buang Air Besar Sembarangan Di Desa Pasar Senin, Desa Kandang Halang, Dan Desa Rantawan Kecamatan Amuntai Tengah Kabupaten Hulu Sungai Utara (Studi Kasus Peraturan Daerah Kabupaten Hulu Sungai Utara Nomor 04 Tahun 2016 Tentang Gerakan Stop Buang Air Besar Sembarangan) - Budiman, Arif; Pratama, Deva Angga (JURNAL BISNIS DAN PEMBANGUNAN, 2023)
The problems that exist are that there are still residents who carry out open defecation activities, there are several latrines along the river, and there is no clear socialization from the government. So the government made North Hulu Sungai Regency Regional Regulation Number 04 of 2016 concerning the Movement to Stop Open Defecation. The aim of this research is to determine the implementation of the stop open defecation movement policy and to find out what factors influence the implementation of the stop open defecation movement policy. The research used is a qualitative approach with a descriptive type. Data collection techniques use interviews, observation and documentation. The data source was taken from 11 informants using purposive sampling. Data analysis techniques using data reduction, data presentation, and drawing conclusions. The results of this research show that the implementation of the Stop Open Defecation Movement Policy in Pasar Rabu Village, Kandang Halang Village, and Rantawan Village, Amuntai Tengah District, North Hulu Sungai Regency is quite good. First, interests that influence clear indicators of policy targets have not been implemented, and the level of policy satisfaction has not been implemented well. Second, the types of benefits with policy benefit indicators have not been implemented, and the continuity and continuity of benefits have not been implemented. Third, the degree of change with indicators of the degree to be achieved is sufficiently implemented. Fourth, the position of policy makers with indicators of accountability for policy implementers has been implemented. Fifth, program implementers with indicators of competence and quality of policy implementers are quite well implemented, and clear communication and coordination of program implementers have been implemented. Sixth, the resources involved with adequate human resource indicators have not been implemented properly, and the supporting facilities and infrastructure have not been implemented. Keywords: Policy on the Movement to Stop Open Defecation, Regional Regulations, Villages